Cut Down to Size at High Noon - Scott Sundby (United Kingdom Random House Distribution childrens, 2000)
The town of Cowlick turns out for a scale-drawing showdown when a tough-talkin' stranger challenges the local hero.
Keywords: Circle Time, Math Stories